2015
DOI: 10.1159/000369927
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Memory Changes in Old Age across Five Years

Abstract: Typically, subjective memory assessments (be it in form of single items or questionnaires) in old age only weakly correlate with the performance in objective memory tests at cross-section. It thus appears as if individual differences in subjective memory assessments hardly reflect individual differences in memory in old age. A shortcoming of cross-sectional studies, however, is that subjective assessments may rely on different individual standards, which are not taken into account. One solution to this problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…There have also been several reports linking higher extraversion, as well as lower neuroticism, to better (long-term) memory performance (Nakamura et al 1979;Ashby et al 1999;Allen et al 2011). Finally, conscientiousness was shown to correlate positively with subjective memory (Pearman 2009), which in turn might reflect performance in objective mnemonic tasks (Zimprich and Kurtz 2015).…”
Section: Association Of Neo-ffi Scores To Gmv In the Male Samplementioning
confidence: 89%
“…There have also been several reports linking higher extraversion, as well as lower neuroticism, to better (long-term) memory performance (Nakamura et al 1979;Ashby et al 1999;Allen et al 2011). Finally, conscientiousness was shown to correlate positively with subjective memory (Pearman 2009), which in turn might reflect performance in objective mnemonic tasks (Zimprich and Kurtz 2015).…”
Section: Association Of Neo-ffi Scores To Gmv In the Male Samplementioning
confidence: 89%
“…While this is consistent with some studies (Cargin et al, 2008; Pearman et al, 2014), several studies, after controlling for depressive symptoms, found correlated longitudinal changes between self-SCC and OM. (Hulur et al, 2015; Parisi et al, 2011; Snitz et al, 2015; Zimprich & Kurtz, 2015). Methodological differences may partially account for some of this inconsistency in that our study included a brief total longitudinal time-frame (mean interval across 3 visits = 4 years), with a relatively healthy and younger cohort (Visit 1 mean = 58 years) that may be exhibiting stable performance on OM compared to older individuals.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Additional limitations include our separate linear mixed effects models approach, as several studies reporting covariation between SCC and OM used latent growth curve modeling (Hulur et al, 2015; Mascherek & Zimprich, 2011; Parisi et al, 2011; Snitz et al, 2015; Zimprich & Kurtz, 2015); which could be particularly useful as our sample ages and likelihood of variability in cognitive function increases. Also, the low test–retest reliability of the IQCODE is inconsistent with previous reliability measurements (Jorm & Jacomb, 1989; Jorm, Scott, Cullen, & MacKinnon, 1991; Jorm, 2004) and again may be partially due to the relatively healthy status and younger age of our sample.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…In these cases, more sophisticated longitudinal analyses could be required to better understand the association between subjective and objective memory. In recent years, several studies have implemented such analyses and examined temporal associations or whether subjective and objective memory changes together over time (Hülür, Hertzog, Pearman, Ram & Gerstorf, 2014;Hülür, Hertzog, Pearman & Gerstorf, 2015;Snitz et al, 2015;Zimprich & Kurtz, 2015). Many of these studies suggest that there are longitudinal associations between changes in subjective and objective memory over time.…”
Section: Subjective and Objective Memorymentioning
confidence: 99%